The Insidious Cardiac Tumor: A Primary Left Atrium Intimal Cardiac Sarcoma in a Young Patient - Chika-Nwosuh Ogechukwu; Nnaoma Christopher; Sossou Christoph; Okundaye Etinosasere; Bustillo Jose (Case Reports in Cardiology)
This case presentation discusses a rare cardiac malignancy initially thought to be a benign tumor. A 36-year-old presented with syncope, dyspnea, Computed Tomography Pulmonary angiography study obtained was negative for pulmonary emboli but revealed a left atrial mass. A transesophageal echocardiogram (TEE) confirmed a mass with multiple lobes and a broad base attached to the septum, encroaching into the right atrium, aortic root wall, base of the anterior mitral leaflet flowing to the mitral orifice in diastole also obstructing the right pulmonary vein. Despite a quick diagnosis and plan to begin treatment, the patient rapidly declined owing to the extent and aggressive nature of this cardiac malignancy. This case reports the insidious nature of these tumors as well as how challenging and life threatening they are at the time of their clinical manifestation.